Chest X-ray Positioning in Suspected Infection in the Emergency Department: Patient Characteristics and Outcome Associations - Bendixen, Sofie Hjort; Ovesen, Stig Holm; Jessen, Marie Kristine; Weile, Jesper (Dansk Tidsskrift for Akutmedicin, 2025)
Introduction: Chest radiography (CXR) is the first-choice imaging for diagnosing suspected infection in the emergency department (ED). However, previous descriptions of x-ray modalities are sparse. The objective was a) to describe CXR modalities in patients with suspected infection, findings, and image quality and b) investigate associations between patient characteristics and modalities. Methods: In this secondary analysis of a prospective cohort study, we included ED patients with suspected infection and a CXR performed while admitted. We used binary regression to investigate which patient characteristics were associated with getting a sitting CXR (sitCXR) or supine CXR (supCXR). Results: Out of 979 included patients, 60% were erect (eCXR), 15% were sitting (sitCXR), and 25% were supine CXR (supCXR). We observed a higher relative risk (RR; 95%CI) of having a sitCXR or supCXR if patients were 60–79 years or >80 years (2.3; 1.7–3.0 or 3.2; 2.5–4.3), had renal failure (1.5; 1.2–1.8), heart failure (1.4; 1.1–1.8), do-not-resuscitate/do-not-intubate-orders (2.5; 2.2–2.8), systolic blood pressure ≤100 mmHg (1.6; 1.3–1.9), respiratory rate ≥22 min (1.4; 1.2–1.6), and saturation <90% (1.6; 1.3–2.0). Conclusion: SitCXR and supCXR are common in ED patients with suspected infection. Patients receiving sitCXR and supCXR were older, comorbid, and presented with abnormal vital signs.